2011
DOI: 10.1016/j.atmosenv.2010.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Emissions of nitrous oxide, nitrogen oxides and ammonia from a maize field in the North China Plain

Abstract: a b s t r a c tThe exchange fluxes of nitrous oxide (N 2 O), nitrogen oxides (NO x ) and ammonia (NH 3 ) from a maize field with three different treatments were simultaneously measured using static and dynamic chambers in the North China Plain (NCP) from June 28 to October 11, 2009. The three treatments included control plot (CK, without crop, fertilization and irrigation), fertilizer N plot (NP) and wheat straw returning plus fertilizer N plot (SN). N-fertilizer application greatly stimulated the emissions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 36 publications
(37 reference statements)
4
45
0
Order By: Relevance
“…The investigated soil in this study is aquic inceptisol which has hydromorphic properties (gley), and denitrification may be more important than that in soils without gley. Our previous study in 2009 (Zhang et al, 2011) from the same field also confirmed that denitrification was the dominant process for N 2 O emission during pre-and post-fertilization period, while nitrification as the dominant process only limited short period after fertilization.…”
Section: N 2 O Emissions From Fertilized Soilmentioning
confidence: 63%
See 1 more Smart Citation
“…The investigated soil in this study is aquic inceptisol which has hydromorphic properties (gley), and denitrification may be more important than that in soils without gley. Our previous study in 2009 (Zhang et al, 2011) from the same field also confirmed that denitrification was the dominant process for N 2 O emission during pre-and post-fertilization period, while nitrification as the dominant process only limited short period after fertilization.…”
Section: N 2 O Emissions From Fertilized Soilmentioning
confidence: 63%
“…The investigation of Liu et al (2003) in the NCP indicated that NO 3 − -N leaching was the main loss pathway in the winter wheat-maize cropping system, which accounted for 67% of total N loss during two cycles of wheat-maize rotation. And we also conducted ammonia volatilization and NO emission during the maize growing season in 2009 (Zhang et al, 2011), the fertilizer loss rates were 1.93% (NP plot) and 0.76% (SN plot) as NO-N, and were 5.24% (NP plot) and 3.03% (SN plot) as NH 3 -N. Therefore, considering nutrient cycling in the agricultural field of the NCP, N 2 O emission is a minor flux compared to the larger leaching, denitrification and ammonia flows. However, N 2 O makes important contribution to current global warming and stratospheric ozone depletion, its emission from agricultural field should not be neglected.…”
Section: N 2 O Emissions From Fertilized Soilmentioning
confidence: 99%
“…NO 2 − has been recognized as the key intermediate product of both nitrification and denitrification, and its further reduction will form NO followed by N 2 O and N 2 (Russow et al, 2009 (Hooper and Terry, 1979;Goreau et al, 1980;Lipschultz et al, 1981;Anderson and Levine, 1986). NO emission from soil is ascribed to nitrification process, and the molar ratio of NO/N 2 O has been used as a useful indicator for evaluating the contribution of nitrification and denitrification to N 2 O emission (Anderson and Levine, 1986;Zhang et al, 2011). However, it is found that the application of the indicator to the field measurements should be careful in our case.…”
Section: Discussionmentioning
confidence: 81%
“…Three opaque static chambers were used for investigating N 2 O emission (Zhang et al, 2011). The chambers (length × width × height: 60 cm × 60 cm × 90 cm) were placed on corresponding pedestals, which were inserted into soil at about 10-cm depth during the whole maize growing period.…”
Section: Measurements and Analysis Of N 2 O No And Nhmentioning
confidence: 99%
“…The North China Plain (NCP), with an area of 35 million hectares, is one of the most important agricultural regions in China (Du et al, 2009). The croplands in the NCP are being treated with increasing amounts of N fertilizer, which can cause increased emissions of N 2 O, NO and NH 3 (Zou et al, 2005;Zhang et al, 2011). Many studies have mainly focused on the gaseous loss of N 2 O from different types of N fertilizer (Cai et al, 2002;Ding et al, 2007;Zhang et al, 2012;Wang et al, 2013), whereas there are few reports about the effect of DCD on N 2 O emission from agricultural fields in this region (Ding et al, 2011;Li et al, 2013;Yan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%